IMAGES AT LARGE I.E. ON ART IN THREE-DIMENSIONAL SPACE, ON THE EXAMPLE OF LESZEK MĄDZIK’S ART - Łarionow, Dominika (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article discusses the work of Leszek Mądziek, focusing mainly on his activities within the framework of the author’s theater of the Artistic Stage of KUL. It has been operating since the 1970s within the administrative structures of the Lublin Catholic University. Mądzik Theater has survived all the economic crises of the 70s and 80s and the social connected with the period of political transformation of the 90s. The artist worked all the time, creating performances with extremely consistent aesthetics. His performances are characterized by a lack of verbal layer, an objectification of the actor and unusual ability to create space using prosaic elements such as wrapping paper, ropes or using different valorisation of the lighting he gains using a large number of spotlights. The author tries to show how the activity of Mądzika, which most critics always placed outside the mainstream of the aesthetics of the Polish theater of the twentieth and twenty-first century, in fact, turns out to be in many cases precursors to, inter alia, the use of new media in the theater or construction of the nameless contemporary hero – an Everyman of new millennium.